CODE-SWITCHING AND CODE-MIXING USED BY GUEST STAR IN HOTMAN PARIS SHOW - Maya Sari; Adip Arifin; Ratri Harida (Journal of English Language Learning, 2021)
Code-switching and code-mixing are the linguistic phenomena that commonly occur in bilingualism society. Code-switching happens when the speakers mix words or phrases from the two languages during the course of speech or conversation. Meanwhile, code-mixing is the change of one language to another within the same utterance or in the same oral or written text. This research aimed to find out the types of code-switching, code-mixing and the reason as well used by Cinta Laura Kiehl as the guest star in Hotman Paris Show television program on January 2nd 2020. This research also aimed to find out the reason of Cinta Laura Kiehl of doing code-switching and code-mixing. The researcher used descriptive qualitative method as the research design. Content analysis and documentation was used as the technique to collect the data. The instruments used were human instrument and documentation sheet. To analyze the data, the researcher used Miles and Huberman (1994) interactive model. The result of the research showed that all the types of code-switching and code-mixing was used by Cinta Laura Kiehl. The most dominant type of code-switching used was intra-sentential code-switching and the most dominant type of code-mixing used was insertion. The most dominant reason of doing code-switching and code-mixing used was to maintain talking about a particular topic.